Distribution, pollution index and associated health risk of trace metals in waste-impacted soils within Akwa Ibom State, Nigeria. Issue 3 (4th May 2018) - Ebong, G. A.; Etuk, H. S.; Dan, E. U.
Abstract: This research assessed the level, source and associated health risks of trace metals in waste-impacted soils within Nigeria. Results reported revealed that mean concentrations for all the metals studied were higher than their levels in control. The mean concentrations of all the metals except Ni were also higher than their recommended limits for Nigerian soil by Federal Environmental Protection Agency. Pollution assessment of these trace metals and different locations studied indicated that Pb and Cd were metals with very high contamination status. Results obtained indicated that concentrations of Fe and Ni were mainly from natural geological processes while Pb, Cd and Cu were from anthropogenic source. Principal component analysis revealed human activities as the major factor for the presence of these metals at the different locations studied. This study identified Ibeno and Uyo as locations with very high soil contamination. Hierarchical clusters and Pearson correlation analyses showed variable relationship among the different locations and metals studied. Results obtained indicated that children in Ibeno and Uyo are in a very high risk developing health problems associated with Pb and Cd. The analytical procedures and results obtained were validated using SRM 2710a (Montan 1 soil.) from NIST, U.S.A.